Experimental investigation on creep behaviour of an epoxy adhesive - Silva, Patrícia Moreira (2015)
Epoxy adhesives have been extensively used in structural strengthening. This leads to a great concern in assessing their long-term performance since epoxy resins present viscoelastic behaviour. This work aims to better understand the long-term behaviour of a specific epoxy adhesive due to the creep effects. Therefore, an experimental program comprising tensile creep tests was carried out, divided in two series: (i) series S1 - epoxy specimens subjected to different stress levels for a predefined initial age; and (ii) series S2 - epoxy specimens subjected to equal stress levels but loaded at different ages. The paper presents the main results obtained so far, highlights relevant and corresponding conclusions.